Robust Measurement Validation in Target Tracking Using Geometric Structure - Yoon, J; Roberts, S (2010)
Selection schemes for forming data validation regions for target tracking are discussed in this paper. We develop a novel algorithm, less sensitive to gate size than conventional approaches. This new gate selection method combines a conventional threshold based algorithm with a geometric metric measure based on the Voronoi diagram. An adaptive search based on the Voronoi measure is then used to select valid data points for target tracking. © 2010 IEEE.